SCIDOT-02. A PHASE I STUDY OF CONVECTION-ENHANCED DELIVERY OF LIPOSOMAL-IRINOTECAN (ONIVYDE) USING REAL-TIME IMAGING WITH GADOLINIUM IN PATIENTS WITH RECURRENT HIGH GRADE GLIOMAS: RESULTS THUS FAR. (11th November 2019) - Kumar, Karishma; Butowski, Nicholas; Aghi, Manish; Bankiewicz, Krystof; Bringas, John; Ann Oberheim Bush, Nancy; Chang, Susan; Clarke, Jennifer; Taylor, Jennie; Martin, Alastair; Berger, Mitchell
Abstract: BACKGROUND: Chemotherapy for high grade gliomas (HGG) is limited by the blood-brain-barrier (BBB). Convection enhanced delivery (CED) improves chemotherapy delivery by utilizing fluid convection obviating the challenges of crossing the BBB while minimizing systemic toxicity. CED of nanoliposomal-irinotecan (Onivyde) showed to be a superior delivery route for anti-tumor activity in animal models. An advance of this trial is the development and use of real time CED, which utilizes MRI to visualize the CED process with the aid of co-convected contrast agents, monitoring delivery into the brain and affording for corrective action. METHODS: This is a 3 + 3 single dose escalation trial with 2 cohorts: 20mg/ml and 40mg/ml. Onivyde and GAD were co-infused via the same catheters in a one-time delivery. The total dose was personalized based on the patient's tumor volume, and ranged from 20–680 mg of Onivyde, given via up to 4 catheters. Tumor diameters were allowed to be 1 – 4 cm, with injection volumes ranging from 2 – 17 mL of infusate. RESULTS: 13 patients have been treated on this protocol, all in under 5 hours. There were 9 GBs, 1 gliosarcoma, 2 AAs, and 1 oligoastrocytoma. Utilizing imaging software, we correlated pre-infusion modeling of the drug distribution with post-infusion imaging. A number of technical challenges were overcome by real time monitoring; the total volume of distribution (Vd), and the Vd to volume infused (Vi) ratio for each infusion was ~2. Of all patients, the only notable AE was encephalopathy, which was resolved. CONCLUSIONS: Image-guided distribution allows for safe real-time placement and adjustment of CED cannula of Onivyde into patient's brains. Such methods allow for maximum tumor coverage and warrant further studies with repeat dosing.